Dynamic coupling of economic and energy structures in resource-based regions: a case study of Shanxi Province, China - Ende Hu; Zeyuan Shen; Xianghua Wang (Sustainable Energy Research)
Abstract Understanding the degree of coupling and coordination between economic structure and energy structure is critical for advancing sustainable regional development, particularly in resource-dependent areas. Drawing on data from Shanxi Province spanning 2010 to 2022, this study constructs comprehensive indicator systems for both economic and energy structures. Employing an improved coupling coordination degree model and the Geographical Detector approach, we assess the temporal and spatial evolution of coupling coordination across municipalities and identify the principal determinants of coordination dynamics. The findings reveal that, although the overall level of coupling coordination in Shanxi’s cities remained relatively low during the study period, a steady upward trend is evident. From 2010 to 2019, adjustments in the economic structure outpaced those in the energy structure, whereas from 2020 onward, the transformation of the energy structure advanced more rapidly than economic restructuring. Significant spatial heterogeneity exists among cities, with Changzhi, Jincheng, and Linfen exhibiting relatively higher degrees of coordination. Consumption structure, employment structure, income structure, and the share of clean energy emerge as key factors influencing the coupling coordination between economic and energy systems. This study provides empirical evidence and actionable policy insights to foster synergies between economic upgrading and energy transition during the sustainable transformation of resource-rich regions.